Assessment of aflatoxin contamination of maize, peanut meal and poultry feed mixtures from different agroecological zones in Cameroon - Kana, J.R.; Gnonlonfin, G.J.B.; Harvey, Jagger J.W.; Wainaina, J.; Wanjuki, I.; Skilton, Robert A.; Teguia, A. (MDPI, 2013)
Mycotoxins affect poultry production by being present in the feed and directly causing a negative impact on bird performance. Carry-over rates of mycotoxins in animal products are, in general, small (except for aflatoxins in milk and eggs) therefore representing a small source of mycotoxins for humans. Mycotoxins present directly in human food represent a much higher risk. The contamination of poultry feed by aflatoxins was determined as a first assessment of this risk in Cameroon. A total of 201 samples of maize, peanut meal, broiler and layer feeds were collected directly at poultry farms, poultry production sites and poultry feed dealers in three agroecological zones (AEZs) of Cameroon and analyzed for moisture content and aflatoxin levels. The results indicate that the mean of the moisture content of maize (14.1%) was significantly (P < 0.05) higher than all other commodities (10.0%-12.7%). Approximately 9% of maize samples were positive for aflatoxin, with concentrations overall ranging from <2 to 42 ?g/kg. Most of the samples of peanut meal (100%), broiler (93.3%) and layer feeds (83.0%) were positive with concentrations of positive samples ranging from 39 to 950 ?g/kg for peanut meal, 2 to 52 ?g/kg for broiler feed and 2 to 23 ?g/kg for layer feed. The aflatoxin content of layer feed did not vary by AEZ, while the highest (16.8 ?g/kg) and the lowest (8.2 ?g/kg) aflatoxin content of broiler feed were respectively recorded in Western High Plateau and in Rainforest agroecological zones. These results suggest that peanut meal is likely to be a high risk feed, and further investigation is needed to guide promotion of safe feeds for poultry in Cameroon.